A comparative analysis of the regulatory and business implications of broadband rollout for the USA and the UK communications industries. (12th May 2004) - Combe, Colin
Broadband services were introduced in the UK from 2002. The development and implementation of the new technology has been fraught with organisational and regulatory problems. UK broadband services have evolved within the government policy framework of liberalising regulation of the communications industries. The aim is to create an industry structure that maximises competitive advantages for UK firms in the global communications market. This paper examines the regulatory and business implications of broadband rollout for the UK firms by undertaking a comparative analysis with the USA where broadband services are already in place within a free market orientated regulatory regime. The analysis exposes the main barriers to the development of broadband services in the UK and also key structural differences between the USA and the UK that constitute the reasons behind the difficulties experienced in launching the new services.